Detection of intestinal microbiota components in the synovial microenviroment of peripheral spondyloarthritis and its association to immunopathogenic mechanisms - Arias, Jose Luis (2021)
A role for intestinal microbes in arthritis is being considered. We analyzed intra-articular microbiota components and their association with immunopathogenic mechanisms of Spondyloarthritis (SpA). Synovial fluid (SF) of peripheral SpA patients were pooled (n=9): 6 psoriatic arthritis, 2 reactive arthritis, 1 undifferentiated SpA (Protocol approved CE002-2017). IL-17, IL-6, IL-23 and TGF-b levels were quantified in each SF sample by ELISA and compared with SF from osteoarthritis (OA). Moreover, SW982 cells (human synovial fibroblasts) were incubated with the SpA SF pool in absence or presence of polymyxin B (LPS inhibitor) and 48 h later the IL-6 levels in the supernatant were measured by ELISA. Furthermore, intestinal microbiota proteins were analyzed in the SpA SF pool through a Gel-LC bottom-up mass spectrometry-based proteomic study. Higher levels of IL-17, IL-6, IL-23 and TGF-b were detected in SpA compared with OA SF (p<0.001, p<0.01, p<0.001, and p<0.01, respectively). Since segmented filamentous bacteria (SFB) have a cardinal feature to induce Th17 cell differentiation in gut immunity, we searched for SFB peptides in the SF of SpA. We found 54 peptides of SFB with abundance estimated with an exponentially modified Protein Abundance Index (emPAI) from 0.01 to 0.28. In addition, LPS is present in synovial microenvironment of SpA since polymyxin B treatment significantly reduced IL-6 secretion by synovial fibroblasts stimulated with SpA SF (p<0.05). Therefore, we explored the synovial presence of peptides of microbiota Gram-negative bacteria, particularly genus Dialister because it was described as a potential intestinal microbial marker of disease activity in SpA. Accordingly, we found 55 peptides of genus Dialister (emPAI 0.02-0.33). Our findings show the presence of LPS and microbiota bacterial proteins in the synovial microenvironment of peripheral SpA and suggest their potential association with immunopathogenic mechanisms of this inflammatory arthropathy.